A Review on Sweep Coverage in Wireless Sensor Networks - Kaur, Gurbax; Sharma, Ritesh (International Journal of Computer Sciences and Engineering, 2025)
There are lots of applications where only periodic monitoring (sweep coverage) is sufficient instead of continuous monitoring. The main goal of sweep coverage problem is to minimize the number of mobile sensor nodes moving with uniform velocity required to guarantee coverage as per given sweep time. In the sweep coverage scenario, deployment of static sensor nodes may partially solve the purpose but it suffers from poor efficiency and unnecessary extra overhead. Moreover, static sensor network suffers from static sink neighborhood problem in which the sensors which lie near to the sink node dies due to which the sink disconnects from rest of the network.